2011
DOI: 10.1016/j.ajpath.2010.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Anti-HIV MicroRNA Expression

Abstract: Several micro RNAs (miRNAs) have the ability to inhibit HIV replication in target cells. Thus, we investigated the impact of opioids (morphine and heroin), widely abused drugs among people infected with HIV, on the expression of cellular anti-HIV miRNAs in monocytes. We found that morphine-treated monocytes expressed lower levels of cellular anti-HIV miRNAs than untreated cells. In addition, morphine treatment of monocytes compromised type I interferon (IFN)-induced anti-HIV miRNA expression. These findings pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 45 publications
(53 reference statements)
1
61
0
Order By: Relevance
“…Mediated largely by IFN-α and IFN-β, type 1 interferon signaling increases cellular resistance to viral infection, facilitates interaction of infected cells with immune cells via increased MHC I expression, and impairs viral replication (Paul et al, 2007). Disruption of IFN-α, β signaling has been observed in morphine-treated human monocytes, leading to increased HIV-1 replication (Wang et al, 2011). Similarly, LP-BM5 infection itself was shown to disrupt the type 1 interferon response in splenocytes and other peripheral organs (Cheung et al, 1991; Pitha and Biegel, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mediated largely by IFN-α and IFN-β, type 1 interferon signaling increases cellular resistance to viral infection, facilitates interaction of infected cells with immune cells via increased MHC I expression, and impairs viral replication (Paul et al, 2007). Disruption of IFN-α, β signaling has been observed in morphine-treated human monocytes, leading to increased HIV-1 replication (Wang et al, 2011). Similarly, LP-BM5 infection itself was shown to disrupt the type 1 interferon response in splenocytes and other peripheral organs (Cheung et al, 1991; Pitha and Biegel, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…However, other in vitro studies showed that morphine decreased Tat-induced production of interleukin (IL)-8 by astrocytes (Reddy et al, 2012) and the production of TNF-α, IL-6, and CCL2/MCP-1 (monocyte chemoattractant protein-1) by microglia (Jadwiga Turchan-Cholewo et al, 2009). Morphine also disrupts type 1 interferon signaling, leading to a dysregulated cellular antiviral response and facilitating increased viral replication (Cheung et al, 1991; Wang et al, 2011). These conflicting results underline the need for further investigation into the effects of morphine in the HIV-1-infected CNS.…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA (1 μg) was subjected to reverse transcription (Promega, Madison, WI). Real-time PCR was performed with the iQ SYBR Green Supermix (Bio-Rad Laboratories, Hercules, CA) as previously described [31, 32]. The oligonucleotide primers were synthesized by Integrated DNA Technologies, Inc. (Coralville, IA) and sequences will be available upon request.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of morphine and heroin on the inhibition of neuron-preferential differentiation were also indirectly proven in SH-SY5Y cells. miR-125b, which increases the differentiation of SH-SY5Y cells with neurite outgrowth [80], is significantly down-regulated by opioids such as morphine and heroin both in vitro and in vivo and is up-regulated during neuronal differentiation [81]. The δ-opioid peptide [ d -Ala 2 , d -Leu 5 ]-Enkephalin (DADLE) shows an anti-proliferative effect, which is derived from its regulation of the cell cycle by causing an arrest of AF5 cell cycle progression at the Gap 1 (G1) checkpoint [82].…”
Section: Modulation Of Nspcs By Addictive Drugs and Underlying Mechanmentioning
confidence: 99%